2016
DOI: 10.1021/acs.langmuir.6b00393
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Nitride Bioceramics Induce Chemically Driven Lysis inPorphyromonas gingivalis

Abstract: Organisms of Gram-negative phylum bacteroidetes, Porphyromonas gingivalis, underwent lysis on polished surfaces of silicon nitride (Si3N4) bioceramics. The antibacterial activity of Si3N4 was mainly the result of chemically driven principles. The lytic activity, although not osmotic in nature, was related to the peculiar pH-dependent surface chemistry of Si3N4. A buffering effect via the formation of ammonium ions (NH4(+)) (and their modifications) was experimentally observed by pH microscopy. Lysis was confir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
85
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 86 publications
(86 citation statements)
references
References 78 publications
0
85
0
1
Order By: Relevance
“…In addition to surface charge and wetting considerations, it has also been recently demonstrated that surface dissolution of Si 3 N 4 also impacts bacterial adhesion and biofilm formation . In the presence of moisture, there is a diffusion‐limited thermodynamic driving force to convert silicon nitride to silicic acid (Si(OH) 4 ) and ammonia (NH 3 ) as indicated in Equation below: Si3N4+12H2O3Si(OHfalse)4+4NH3 ΔG 298°K = 565 kJ/mol …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to surface charge and wetting considerations, it has also been recently demonstrated that surface dissolution of Si 3 N 4 also impacts bacterial adhesion and biofilm formation . In the presence of moisture, there is a diffusion‐limited thermodynamic driving force to convert silicon nitride to silicic acid (Si(OH) 4 ) and ammonia (NH 3 ) as indicated in Equation below: Si3N4+12H2O3Si(OHfalse)4+4NH3 ΔG 298°K = 565 kJ/mol …”
Section: Discussionmentioning
confidence: 99%
“…The release of NH 3 from the Si 3 N 4 surface not only increases the local pH to ≈8.5, which deleteriously affects bacteria adhesion, but it also affects their metabolism in a manner similar to the elution of nitric oxide (NO) from xerogel polymers . Charville et al demonstrated this in a study which examined the effect of NO release from fibrinogen‐mediated xerogel coated glass slides on the adhesion of S. aureus , S. epidermidis , and E. coli .…”
Section: Discussionmentioning
confidence: 99%
“…It is speculated that nitrogen scavenging occurred through NH 4 + uptake driven by the membrane potential. Previously, pH microscopy experiments demonstrated that ammonia formation and pH buffering readily occurs at the surface of Si 3 N 4 when exposed to a biological environment20. Surface alkalization might also play a role in enhancing the metabolic uptake of nitrogen50.…”
mentioning
confidence: 99%
“…Cells metabolically assimilate and transform water, carbon dioxide (CO 2 ), and three inorganic nitrogen compounds – ammonium (NH 4 + ), nitrate (NO 3 − ), and di-nitrogen (N 2 ) – into complex biomolecules19. One of the more obvious and yet intriguing aspects involving the use of silicon nitride as a biomaterial is that H 4 SiO 4 , NH 4 + , NO 3 − , and N 2 are all promptly and copiously available during biological interactions20. The peculiar chemistry of Si 3 N 4 , which can be chemically-modulated21, facilitates a range of favorable metabolic interactions between both eukaryotic and prokaryotic cells at its inorganic surface820.…”
mentioning
confidence: 99%
See 1 more Smart Citation